Curriculum rebirth a research-based curriculum enrichment plan for the AB in Communication Arts program of the University of the East-Caloocan - Suarez, Vida Socorro Esguerra 1972- (2008)
"Curriculum Rebirth: A Research-Based Curriculum Enrichment Plan for the AB in Communication Arts Program of the University of the East Caloocan Campus" is a two-phase thesis that started with a quantitative-qualitative evaluation study of the present curriculum and ended with a proposed new AB in Communication Arts Program that aims to be responsive to the need of its various stakeholders: the academe, alumni, graduating students and communication and communication-related professions. Results of the study revealed that graduates from Batches 2001 to 2006 were mostly employed, with one-third of them working in the filed of communication. Meanwhile, most graduating students would like to pursue film, broadcasting and advertising after graduation. On the other hand, alumni respondents would still like to pursue careers in communication and communication-related professions. Most respondents regarded all major subjects and most minor subjects both relevant for employment in communication and communication-related professions. They also considered all concepts important, all skills very important and all traits very important for employment. Focus group discussants assesses the development of these concepts, skills, and traits as very good and very relevant in their current and/or future career tracks. Majority of faculty members preferred a generalist program that will talk about the different facets of communication. They still preferred the title AB in Communication Arts. In general, results of the study showed that the AB in Communication Arts Program of the University of the East-Caloocan has moderately prepared its students in communication and communication-related professions. The present curriculum is moderately relevant to the job requirements of employers in communication and communication related profession and to the career tracks that alumni and graduating students would like to pursue. Based on the evaluation, the researcher developed a curriculum enrichment plan to address the concerns of all stakeholders. It is a new AB in Communication Arts curriculum that not only focuses on Broadcasting but on the different areas of communication, particularly, mass communication. It aims to develop among the students the concepts, traits and skills required for them to be employed in communication and communication-related profession; develop and instill in them the process of doing research as their contribution to the discipline; and develop and instill in them a sense of responsibility towards their audiences and the significant contribution that they can give to their immediate communities and to society through their work. This study is entitled "Curriculum Rebirth" because it hopes to give a new definition and perspective to the program title AB in Communication Arts of the University of The East Caloocan Campus with the vision of honing students to become globally competitive, adaptive, responsive, and conscientious communication specialists and media practitioners in the years to come."